IKLIM ORGANISASI DAN PENGARUH TERHADAP KINERJA GURU SMA (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2006)
The purpose of this research is to find out the of organizational climate (Flexibility comformity, responsibility, standards, rewards, clarity and tema commitment) on job employees in Surabaya. Sample in this research was taken fmm seven schools in Surabaya, totally amounting to 93 respondent. Analytical technique that used was multiple linear regression with SPSS program and the result is flexibility comformity, responsibility, standards, rewards, clarity and tema commitment variable has significant effect on job employees simultanly or partially, which is reward variable has dominant effect.